Metamaterial loaded circular ring micro strip antenna with CSRR as ground plane for 5g applications - Magthelin Therase, L.; Jayanthy, T. (International Journal of Engineering and Technology, 2018)
This paper presents a miniaturized UWB antenna with metamaterial for WLAN and Ku band applications. Miniaturization is obtained using metamaterial loaded ground structure (CSRR) and surface wave losses improved using EBG structures. The physical dimension of the antenna is 20 mm x 20 mm. In unloaded condition the antenna resonates at single band. When the same antenna is loaded with CSRR in the ground plane, it resonates at different frequencies which are used to achieve 5G applications which is the demand of current technology. The Metamaterial based antenna is designed for some improvement in the performance of directivity gain, return loss and size of circuit area. A patch antenna has been designed and fabricated to operate between 9GHz-16GHz.Â Â